Practicing Agroecology: Management Principles Drawn From Small Farming in Misiones (Argentina) - Girard, Nathalie (2015)
In face of sustainability challenges, agronomical research has focused on the design of new production systems, whereas ethnographic studies have put forward the traditional small production systems. A gap remains between such agroecological design and the practices of farms. Our objectives are to draw principles for agroecological management from the in-depth study of practices in ecologically based farms in Argentina. We extracted three principles: 1) adjustment and observation instead of control, 2) variable and flexible management in time and space, and 3) permanent at-home experimentation. After examining their generality, we discuss the paths to take these systems as models for the ecologization of conventional systems.